Gustaw Herling e Elémire Zolla: tracce di un’amicizia - Bruni, Raoul; Ślarzyńska, Małgorzata (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
The aim of this article is to show the relationship between Gustaw Herling-Grudziński and Elémire Zolla through their letters, until now unpublished, kept in the Archive of Herling-Grudziński in Naples. The letters sent to Herling-Grudziński by Zolla are published here for the first time. The literary relation between the two writers and intellectualists can also be traced in Zolla’s review of Herling-Grudziński’s volume of short stories Pale d’altare, translated into Italian and published in Italy, as well as in Herling’s-Grudziński review of Zolla’s novel Cecilia o la disattenzione.